Pretty in pink [videorecording (DVD)] - Hughes, John, 1950-2009; Ringwald, Molly; Stanton, Harry Dean, 1926-2017; Cryer, Jon, 1965-; McCarthy, Andrew, 1962-; Spader, James; Potts, Annie (Paramount Home Entertainment, 2006)
A poor girl falls in love with a rich guy, and it angers both their families and their friends.